2010
DOI: 10.1111/j.1464-410x.2010.09885.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Treatment Costs of Organ‐confined Prostate Cancer: A General Perspective

Abstract: REFERENCES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There has been a steady rise in technological refinements in surgery (laparoscopic or robot assisted) and radiotherapy (intensity modulated radiotherapy, brachytherapy, stereo-tactic radiotherapy) with varying degrees of success in reducing morbidity of treatment [2,3]. All have led to rising costs [4].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a steady rise in technological refinements in surgery (laparoscopic or robot assisted) and radiotherapy (intensity modulated radiotherapy, brachytherapy, stereo-tactic radiotherapy) with varying degrees of success in reducing morbidity of treatment [2,3]. All have led to rising costs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similar proven efficacy in terms of overall survival [ 7 ], these treatments differ substantially in their side effects pattern [ 8 11 ]. With so many different alternatives, health economics may contribute with relevant information for decision-making on treatment for localized prostate cancer [ 12 ], and there has been an increasing number of economic evaluations worldwide: comparing surgery versus radiotherapy [ 13 , 14 ], different variations of prostatectomy [ 13 , 15 17 ] or radiotherapy [ 13 , 14 , 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that different approaches are associated with variations in post-operative recovery and length-of stay (LOS) [16]. These developments might be expected to have impacted on LOS, but population-level data is limited.…”
Section: Introductionmentioning
confidence: 99%